2020
DOI: 10.21203/rs.3.rs-39006/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessment of irreducible aspects in developmental hip dysplasia by magnetic resonance imaging

Abstract: Background: The developmental dysplasia of the hip (DDH) can cause a wide range of pathological changes, and often requires surgical treatment. Preoperative evaluation is very important for DDH. We aimed to assess the diagnostic capability of magnetic resonance imaging (MRI) for irreducible aspects preventing hip reduction in DDH. Methods: A total of 39 pediatric patients who received DDH evaluation in pediatric orthopedics from January 2015 to December 2019 were included. The samples included 4 cases of bilat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…1,2 MRI can clearly detect these abnormalities in all of bony, cartilaginous and soft-tissue structures without radiation exposure and hence is increasingly being used to assess the quality of hip reduction in infantile DDH. [1][2][3][4] Gradual reduction (GR) using traction followed by spica casting is one of the non-surgical procedures for hip dislocation in infant and toddler. Several researchers have reported that GR using traction reduces the failure of reduction and the risk of avascular necrosis of the femoral head while having a slightly higher rate of residual acetabular dysplasia, compared with closed reduction (CR) by manual manipulation.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 MRI can clearly detect these abnormalities in all of bony, cartilaginous and soft-tissue structures without radiation exposure and hence is increasingly being used to assess the quality of hip reduction in infantile DDH. [1][2][3][4] Gradual reduction (GR) using traction followed by spica casting is one of the non-surgical procedures for hip dislocation in infant and toddler. Several researchers have reported that GR using traction reduces the failure of reduction and the risk of avascular necrosis of the femoral head while having a slightly higher rate of residual acetabular dysplasia, compared with closed reduction (CR) by manual manipulation.…”
Section: Introductionmentioning
confidence: 99%